Türkiye’de Reel Döviz Kuru ile İhracat ve İthalat Arasındaki Nedensellik İlişkisinin Analizi (2003-2017) - Erdil Şahin, Begüm (My University, 2017)
In this study, the relationship between real exchange rates and imports and exports was investigated by means of VAR analysis using monthly data for the period of 2003: 01-2017: 08. In the study; "Stationary Test, VAR Model, Co-integration Analysis, Error Correction Model and Granger Causality Test" methods were conducted respectively to examine the relationship empirically. The results have shown that any change in the real exchange rate has no significant effect on imports and exports and real exchange rate cannot be used to balance international trade effectively. On the other hand, a causality relationship was determined between imports and exports.
Keywords: Real Exchange Rates; Export; Import; Co-integration Analysis; Causality Analysis